Taxonomy of the genus Aporcelaimellus Heyns, 1965 (Nematoda, Dorylaimida, Aporcelaimidae) - Álvarez-Ortega, Sergio; Peña-Santiago, Reyes (Zootaxa, 2013)
The taxonomy of the genus Aporcelaimellus is revised and updated. A new definition is proposed, with several remarkable diagnostic characters: cuticle three-layered, especially distinguishable at caudal region, usually bearing a hyaline space between inner and intermediate layers at terminal portion of tail; cervical lacunae often present and well developed; oral aperture a dorso-ventral, hexagonal open slit; lip region showing bilateral symmetry and offset by a more or less distinct constriction; odontostyle short, robust and with wide aperture; uterus simple, bi- or tripartite; pars refringens vaginae present, well developed; tail similar in both sexes, short, rounded to conical with more or less rounded terminus; and ventromedian supplements 7–25 in number, separated, almost always with pre-cloacal space (hiatus). A list of 28 valid species and their synonyms is provided as well as a key to their identification and a tabular compendium of their morpho-metrics. Aporcelaimellus faridpuriensis is considered to be a species inquirenda. Twenty-one species are regarded as in-certae sedis: A. amplexor, A. budauniensis, A. canis, A. digicaudatus, Dorylaimus domus glauci, A. estonicus, A. gerlachi, A. goldeni, A. index, A. jairajpurii, A. monodelphus, A. nawabganjense, A. nivalis, A. paracentrocercus, A. paraobtusicau-datus, A. radicus, A. sacchari, A. seinhorsti, A. stilus, A. submissus and A. subsimilis. Two species are retained under other genera: A. bicuticulus under Labronema, and A. cocophilus under Aporcelaimus. Sixteen species are transferred to other genera: A. baqrii and A. odhneri to Crassolabium; A. dubius to Discolaimium as Discolaimium geraldi nom. n.; A. duhouxi to Labronema; A. glandus, A. heynsi, A. maitai and A. paraconicaudatus to Discolaimium; A. insularis, A. jiaonanensis, A. kikereensis and A. propinquus to Aporcelinus; A. maximus to Aporcella; A. paracentrocercus apud Andrássy (1960) to Aporcelinus as Aporcelinus africanus sp. n.; A. saprophilus to Eudorylaimus; and A. tritici to Makatinus. Finally, A. con-cavus becomes a non-valid binomen.